Them that follow [videorecording (DVD)] - Poulton, Britt; Savage, Dan Madison; Colman, Olivia; Dever, Kaitlyn; Englert, Alice, 1994-; Gaffigan, Jim (Lionsgate, 2019)
Deep in Appalachia, Pastor Lemuel Childs officiates over an isolated community of serpent handlers, an obscure sect of Pentecostals who freely take up venomous snakes to prove themselves before God. As his devoted daughter Mara prepares for her wedding day under the observant eye of Hope Slaughter, Mara reveals a deadly secret that threatens to shatter the entire community.